Equilibrium Displacement Models Theory, Applications, & Policy Analysis - Brester, Gary W; Atwood, Joseph A; Boland, Michael A (Open textbook library., 2023)
Applied economists frequently use equilibrium displacement models (EDMs), also termed linear elasticity models, for policy analyses because they can be used to estimate changes in prices and quantities that result from exogenous economic or policy shocks. These models are also widely used to estimate changes in producer and consumer surplus caused by exogenous economic shocks and to quantify the short- and long-term impacts of a variety of economic and regulatory actions across multiple markets. For the first time, a textbook that contains all of the theory and applications of EDMs along with a set of spreadsheet files is available in one place.